The Modified THP-1 Activation Assay for the In Vitro Identification of Drug-Inducing Systemic Hypersensitivity - Iulini, Martina; Maddalon, Ambra; Galbiati, Valentina; Corsini, Emanuela (Frontiers in Toxicology, 2022)
The development of new low molecular weight drugs has many chances of failure and is an expensive process. Currently, there are no screening methods and/or models to assess the risk of hypersensitivity reactions to drugs (DHRs) in the preclinical phase. DHRs represent 6-15% of adverse drug reactions. The lack of preclinical models has led to withdrawing drugs from the market and treating unexpected reactions on patients with a high cost for the society. The mechanism of hypersensitivity reactions is extensively studied, despite the importance of drug-induced adverse reactions directly related to immune-mediated hypersensitivity and autoimmunity reactions, there are no in vitro or in vivo sensitive models able of predicting the sensitizing potential of drugs in the preclinical phase. This article describes a novel approach methodology (NAM) for the study of the sensitizing potential of drugs based on the use of the human promyelocytic cell line THP-1 as a surrogate of dendritic cells. The method is based on the upregulation of specific surface markers (CD86 and CD54) and on the production of interleukin-8. In our experience, the THP-1 activation assay allowed the correct identification of drugs known to induce systemic hypersensitivity in humans, including the one associated with specific HLAs. This method may help to discover possible systemic hypersensitivity reactions early in the preclinical phase of drug development.